Faktor- Faktor yang Mempengaruhi Ketahan Pangan di Sumatera Barat - Evalia, Nur Afni; Budiman, Cipta; Triana, Lora; Evaliza, Dwi; Fitriana, Widya (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Food security is a strategic issue in sustainable development, encompassing the dimensions of availability, access, and utilization of food. This study aims to examine the influence of socio-economic variables on food security levels in West Sumatra Province. A quantitative explanatory approach was applied using multiple linear regression (Ordinary Least Squares/OLS) based on 174 secondary data observations from official sources. The independent variables analyzed include the normative consumption-to-availability ratio (NCPR), poverty rate (Pove), food expenditure share (PP), electricity access (TL), clean water access (TAB), average years of female schooling (LSP), population-to-health worker ratio (RTK), stunting prevalence (STUN), and life expectancy (AK). The study reveals that seven out of nine examined variables have a statistically significant impact on food security, with a high coefficient of determination (R² = 0.8817), indicating a strong explanatory power of the model. These findings underscore that food security is not solely determined by the availability of food but is also deeply influenced by broader structural factors such as poverty levels, educational attainment, and access to essential public services. The core implication of this research is the necessity for holistic and localized policy responses. Addressing food security requires not just increasing food supply, but also reducing socioeconomic disparities and improving infrastructure and education, tailored to the specific conditions of each region to ensure sustainable food resilience.